ANALISIS PENDAPATAN USAHA TEMPE “BU WARTI” DI KELURAHAN MENTAOS BANJARBARU - Triatmoko, Eddy; Refiana, Fenny; Fitriadi, Subhan (Fakultas Pertanian UVAYA Banjarmasin, 2025)
The purpose of this research is to know the revenue,the Variable cost and ,income. This research was conducted in September – November 2025 at mentaos village, Banjarbaru regency. The study case sampling methode used was by observing Tempe Bu Warti in Mentaos . Average result of the revenue is Rp. 94.000.000.,/month The average Variable cost is Rp. 70.192.175/month, and Average income Rp. 23.807.825/month, and From this result of development of farming Tempe .We believe that it has good prospect and revenue, of the average income ,tecnicall,economically and increase in Tempe Business